Publication Opportunities of Non-research Articles in Health - Joel Rey Ugsang ACOB; Heru Santoso Wahito Nugroho; Tanko Titus Auta (Humanistic Network for Science and Technology (HNST), 2021)
The pandemic may isolate researchers, but is not ceasing the desire to generate newer concepts as effective material to publish. This manuscript epitomizes non-research articles in health which are promising to sustain the generation of ideas and knowledge in the absence of the conventional research process through outdoor surveys.Keywords: publication; health; non research article